2009
DOI: 10.1007/s10535-009-0020-4
|View full text |Cite
|
Sign up to set email alerts
|

Developmental expression of β-glucosidase in olive leaves

Abstract: Plant β-glucosidases catalyze the hydrolysis of glycosidic linkages and play a vital role in defense against pathogens and stress. The present work investigated the relationship between leaf development and β-glucosidase protein content in Olea europea L. (cv. Picual) leaves. The total chlorophyll content increased with leaf age in current-season leaves. Immunoblot analysis revealed that the content of 61 kD protein of β-glucosidase also increased with leaf age, and that the enzyme existed in three isoforms (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
(12 reference statements)
0
11
0
Order By: Relevance
“…The entire olive genome sequence is still unknown, yet olive trees like other plants probably contains many β-glucosidases of diverse as well as similar functions and substrate specificities. Indeed, in both olive leaves and fruit mesocarp, a number of β-glucosidase isoforms have been detected (Mazzuca et al, 2006;Wang et al, 2009). Thus, although Southern blot analysis showed that OeGLU cDNA is encoded by a single-copy gene in the olive genome, it should be noted that hybridization was conducted under high-stringency conditions and therefore the occurrence of other isozymes hydrolysing oleuropein cannot be excluded.…”
Section: Oleuropein Hydrolysis and Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…The entire olive genome sequence is still unknown, yet olive trees like other plants probably contains many β-glucosidases of diverse as well as similar functions and substrate specificities. Indeed, in both olive leaves and fruit mesocarp, a number of β-glucosidase isoforms have been detected (Mazzuca et al, 2006;Wang et al, 2009). Thus, although Southern blot analysis showed that OeGLU cDNA is encoded by a single-copy gene in the olive genome, it should be noted that hybridization was conducted under high-stringency conditions and therefore the occurrence of other isozymes hydrolysing oleuropein cannot be excluded.…”
Section: Oleuropein Hydrolysis and Activationmentioning
confidence: 99%
“…This is accomplished by the recognition and discrimination of the aglycon moiety of the substrate (Czjzek et al, 2000;Verdoucq et al, 2003Verdoucq et al, , 2004. Olive, like other plants, contains a number of different β-glucosidases as recent proteomic and transcriptomic studies have shown (Wang et al, 2009;Alagna et al, 2012;Corrado et al, 2012;Bianco et al, 2013). Romero-Segura et al (2009) reported the purification of a β-glucosidase enzyme from mature olive fruit that was able to hydrolyse olive glucosides and exhibited high substrate specificity to oleuropein.…”
Section: Introductionmentioning
confidence: 99%
“…The degradation products of oleuropein may differ depending on the type of enzyme that acts on this compound. βglycoside (EC 3.2.1.21) forms oleuropein aglycone or decarboxymethyl oleuropein aglycone, through the release of glucose; while esterase's produce glucosyl derivatives, such as hydroxytyrosol and elenolic acid, through the hydrolysis of ester bonds present in oleuropein (Wang et al, 2009). Oxidoreductases, peroxidases and polyphenol oxidases, promote browning through the oxidation of o-dihydroxy phenols to o-quinones (Segovia-Bravo et al, 2009).…”
Section: Biosynthesis and Degradationmentioning
confidence: 99%
“…Different products can be derived from oleuropein according to the type of the enzyme. The b-glucosidase (EC 3.2.1.21) releases glucose forming principally the aldehydic form of oleuropein aglycon (3,4-DHPEA-EA) and the dialdehydic form of decarboxymethyl oleuropein aglycon (3,4-DHPEA-EDA), while esterases hydrolyze the ester bonds of oleuropein, producing glucosyl derivates, hydroxytyrosol (3,4-DHPEA) and elenolic acid (Briante, Patumi, Febbraio, & Nucci, 2004;Mazzuca et al, 2006;Wang, Li, & Hu, 2009). Among the oxidoreductase enzymes, the most relevant are certainly peroxidase and polyphenoloxidase (PPO); the latter is known to catalyze the oxidation of o-dihydroxyphenols to o-quinones that successively condense to form the dark pigments typical of the enzymatic browning (Garcia-Garcia, Segovia-Bravo, Lopez-Lopez, Jaren-Galan, & Garrido-Fernandez, 2009;SegoviaBravo, Jaren-Galan, Garcia-Garcia, & Garrido-Fernandez, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Olive leaves are a copious by-product deriving from olive tree cultivation and olive oil mills that currently are burned, let rot on the ground and only marginally used as animal feed or for phytotherapy (El & Karakaya, 2009). Several researches have revealed the high potential of olive leaves as source of phytochemicals (Briante, Patumi, Terenziani, et al, 2002;De Leonardis, Aretini, Alfano, Macciola, & Ranalli, 2008;Jemai, Bouaziz, Fki, El Feki, & Sayadi, 2008;Pereira et al, 2007), while the recovery of their enzymes has been poorly investigated, although the presence of key enzymatic activities in the plant leaves has been repeatedly evidenced (Briante et al, 2004;Dignum, Kerler, & Verpoorte, 2001;Li, Jiang, Wan, Zhang, & Li, 2005;Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%